Silver Nanoparticles: Technological Advances, Societal Impacts, and Metrological Challenges - Calderón-Jiménez, Bryan; Johnson, Monique E.; Montoro Bustos, Antonio R.; Murphy, Karen E.; Winchester, Michael R.; Vega Baudrit, José R. (Frontiers in Chemistry, 2017)
Silver nanoparticles (AgNPs) show different physical and chemical properties compared to their macroscale analogs. This is primarily due to their small size and, consequently, the exceptional surface area of these materials. Presently, advances in the synthesis, stabilization, and production of AgNPs have fostered a new generation of commercial products and intensified scientific investigation within the nanotechnology field. The use of AgNPs in commercial products is increasing and impacts on the environment and human health are largely unknown. This article discusses advances in AgNP production and presents an overview of the commercial, societal, and environmental impacts of this emerging nanoparticle (NP), and nanomaterials in general. Finally, we examine the challenges associated with AgNP characterization, discuss the importance of the development of NP reference materials (RMs) and explore their role as a metrological mechanism to improve the quality and comparability of NP measurements.